PELATIHAN APLIKASI MICROSOFT EXCEL PEMBUATAN SLIP UPAH KARYAWAN PADA UMKM KULINER PASAR LAMA KOTA TANGERANG - Nurhalim, Andres Dharma (Publika Citra Media, 2025)
Small, Micro and Medium Enterprises (SMEs) are part of one of the backbones of the economy of the people in the city of Tangerang, especially in the old market area. This area is one of the largest centers famous for culinary. Culinary SMEs in the area still use simple systems and technologies in running their businesses including production, administration, marketing, financial records and payroll. The purpose of this community service activity is to provide and introduce how to make pay slips to help compile and provide transparency of salaries/wages for employees in Culinary SMEs in Tangerang City. Community service is carried out face-to-face in the form of presentations and practice (tutorials) on making pay slips, presentations using Microsoft Office Powerpoint and Microsoft Office Excel applications. Participants in the community service activity are representatives of culinary SME business actors in the city of Tangerang and fellow participants in this Community Service (PKM). The implementation of community service received enthusiasm from the participants because it was in accordance with the conditions of business actors and could be applied immediately easily and cheaply.